Combined Sensitivity of T2K-II and NOνA Experiments to CP Violation in Lepton Sector - Ngoc, Tran Van; Son, Cao Van; Van, Nguyen Thi Hong (Communications in Physics, 2018)
In this paper, we study the combined sensitivity of T2K-II and NOvA, the world leading long-baseline neutrino oscillation experiments, to CP violation in lepton sector. By operating until the year 2026, T2K-II is expected to collect a total exposure of \(20 × 10^{21}\) protons-on-target. Meanwhile, NO$ u$A experiment plan to expend the run up to 2024. By combining T2K-II and NO\( u\)A with an ultimate constraint from reactor, the sensitivity to CP-violation is expected to exceed $4σ$ C.L. It is also pointed out that by reducing the systematic uncertainties of both T2K-II and NO$ u$A to a level of 2%, the sensitivity to CP-violation will significantly increase with a discovery possibility at 5$σ$ C.L. significance for a particular range of true \(δ_{CP}\).